Modulação de sinal GNSS focado ao Sistema Europeu Galileo - Maldaner, Liége (2019)
The Global Navigation Satellite System (GNSS) aims to determine the accurate geolocation of a receiver, using a set of signal from the satellites, which transmitted signals vary the modulation according to the constellation. For example, the future European GNSS system Galileo, which will be full operational by 2020, uses modulations that can still be upgraded, such as BPSK (Binary Phase Shift Keying), BOC (Binary Offset Carrier) the AltBOC (Alternative BOC) and MBOC (Modified BOC). GNSS is used in many activities with different levels of accuracy. For example, the monitoration of structures of bridges and viaducts; Georeferencing data of rural properties; Topographic surveying; Communication systems; Time synchronization; Precision agriculture collecting and analyzing data, mapping the area, defining the area of planting. In addition, the GNSS system is essential for the future use of standalone vehicles, which require high liability and accuracy for localization. In this context, this research, presents a detailed description of the main modulation schemes used in the Galileo system. The BPSK, BOC, AltBOC and MBOC modulations were implemented in MATLAB and evaluated on an AWGN channel, considering different spectral spreading codes, and the BER (Bit Error Rate) by SNR (Signal to Noise Ratio) curves were obtained. The results show that the higher the number of bipolar values (-1 or 1) used in the spectral spreading code, the greater the robustness of the system, as expected. In addition, from the results of the autocorrelation function of the BPSK and BOC modulations, it is possible to verify that the BOC modulation has two lateral peaks at the central peak, obtaining three peaks. If these peaks are above the threshold in the tracking process of the receiver to the satellite signal, there may be an error state to the receiver, when instead of detecting the central peak, it detects one of the sides. The same peaks occur in the AltBOC and MBOC modulations, however, to a lesser extent. In addition, in the frequency domain modulation analysis, BOC modulation has two main peaks which power is smaller than the lateral peaks, so the use of this modulation in the E6P band (1278.75 MHz) does not interfere with the GLONASS BPSK signal that is transmitted in the same band. The spectrum of the constant envelope AltBOC modulated signal in the E5 band (1191,795 MHz) is similar to two BPSK signals duplicated at 15 MHz to the left and right of the carrier frequency. Thus, the BPSK-modulated GPS signal, which uses the L5 band contained in the E5 band, does not interfere with the entire spectrum of the AltBOC signal. Finally, the spectrum of the MBOC modulated signal, with respect to the BOC signal, has two main peaks of greater power compared to the lateral peaks. This signal is used by Galileo in the E1 frequency band (1575.52 MHz), which is shared by the GPS BOC signal. Thus, the peaks of both signals, BOC and MBOC do not significatively interfere themselves.